Computational Model of Cultural Preservation based on Cellular Automata. Issue 4 (March 2021) - Shu, Zeliang; Zhang, Xinmiao; Jiang, Hanlin
Abstract: The competition and integration of cultures is an unavoidable trend in the context of globalization, and immigration behavior has significantly accelerated the process of cultural transmission and integration. Cultural change is an evolutionary process in a complex social system. At present, scholars in this field mainly use the complex network model, Axelrod's cultural communication model, and cellular automata model to simulate the evolution of culture. The process of. Among them, the cellular automaton is a mathematical model with discrete time, space, and variables. Based on the above characteristics of the model, the affected population can be divided into small rectangular units, and time can be divided into units at the same time. Effectively simplified the simulation process.